Evaluation of the fracture strength of ultra-thick diamond plate by the three-point bending ISO standard method. Issue 12 (15th June 2022) - An, Kang; Li, Shiyu; Shao, Siwu; Liu, Peng; Liu, Jinlong; Chen, Liangxian; Wei, Junjun; Zheng, Yuting; Liu, Qing; Li, Chengming
Abstract: In this study, standard diamond bars were prepared using an ultra-thick diamond plate, and the bars had sizes consistent with the International Organization for Standardization (ISO) 14704:2016(E) three-point bending method for measuring the fracture strength. Ultra-thick diamond plate with dimensions of 125 mm (diameter) × 6.5 mm (thickness) were deposited using direct current arc plasma jet chemical vapour deposition. After cutting, grinding, and polishing, 12 diamond bars meeting the requirements of the ISO standard were prepared (36 mm × 4 mm × 3 mm) and tested for fracture strength using the cited ISO standard and elastic modulus using deflection measurements. The fracture strength of the ultra-thick diamond plate was found to be 580 ± 66 MPa. In addition, for comparison, the fracture strengths of standard ZnS, sapphire, and alumina were also analysed. Crucially, this is the first report of the fracture strength of standard-sized diamond plate. The effects of the defects and grain size on the crack formation and failure of the diamond film were analysed. The diamond's fracture strength was affected by the sample thickness, which caused the gradual accumulation of defects as this dimension increased, but not by its length and width. The elastic moduli of sapphire and alumina were compared. Overall, the measurement of the fracture strengths of ultra-thick diamond plate via the ISO standard is important for industrial applications.